Prospecção de instrumentos hidrológicos para apoio à gestão em ambientes urbanos - Angnes, Fabiana Beatris (2004)
small municipalities, provokes various prejudices on environment, mainly in relation to hydric resources quality. Due to lack of infrastructure on draining, water courses are the destiny of the drains, most of the time, without previous treatment. Much of times the reality of urban environments makes unfeasible the establishment of monitoring on many control points for financial or weather questions. On this case, the utilization of simplified methods of the flows estimate makes necessary. On this work, the applicability of the three simplified methods to the flow estimate on urban environment was evaluated. There are: area proportion method, flow proportion method and rain-flow simulation. The first and the second presented flow estimates are similars as the observed ones. However, the utilization of those methods do not dispense a minimum of monitoring events for its comparison. With relation to the utilization of the rain-flow model, was checked the inclusion necessity of the external parameter on the hydric balance, provoked for the water inclusion originated of the domestic drains threw on water body. This model modification presented more closed results of the physics reality. Other aspect treated on this work has to do with impacts diagnosis caused for domestic drains on the hydric resources and the detection of the production sources. From the results obtained, was observed that the water quality flowed in UFSM campus is strongly dependent of the polluted load contribuitions of the amount sub-basin, having on view the high values checked through monitoring program.